Employer attractiveness and corporate reputation as brand signals: A dual-stage inspiration pathway to job pursuit intention - Nguyen, Khoa Huu Dang; Nhung, Ha Hong; Anh, Nguyen Phuong; Quyen, Khong Thi Tu (Edelweiss Applied Science and Technology, 2025)
This study examines how employer brand signals influence job pursuit intention among Generation Z job seekers in a developing-country context. The purpose is to clarify how corporate reputation and employer attractiveness evoke and sustain inspiration that motivates application behavior. Drawing on Signaling Theory, Person–Organization Fit, and Social Identity perspectives, the study proposes a dual-stage inspiration mechanism in which an evoked ("inspired-by") state precedes a motivational ("inspired-to") state. Data were collected from 420 respondents in Ho Chi Minh City and analyzed using partial least squares structural equation modeling (PLS-SEM) with 5,000 bootstrap resamples. The results indicate that both corporate reputation and employer attractiveness positively influence evoked inspiration, which strongly predicts motivational inspiration, leading to higher job pursuit intention. The model explains 42 percent of the variance in motivational inspiration and 51 percent in job pursuit intention. The findings confirm that employer brand signals inspire rather than merely inform potential applicants. Practically, organizations should design reputation and attractiveness strategies that evoke both admiration and motivation, thereby strengthening employer appeal and converting positive perceptions into concrete application intentions.